Halal Lifestyle sebagai Tren Global: Dampaknya terhadap Perkembangan Industri Halal di Indonesia - Sahal Mustajab (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to identify the main characteristics of the halal lifestyle as a global trend and to analyze its impact on the development of the halal industry in Indonesia across various subsectors, including food and beverages, cosmetics/pharmaceuticals, fashion, tourism, and Islamic finance. Using a qualitative approach with a descriptive-analytical method, this research is based on a systematic literature review of reputable journal articles, international halal industry reports, and policy documents from relevant institutions. The findings reveal that the halal lifestyle is no longer merely a religious obligation but has evolved into a global consumption phenomenon that integrates spiritual, ethical, and quality values. This trend has expanded opportunities for Indonesia’s halal industry by increasing awareness among both Muslim and non-Muslim consumers who perceive halal products as symbols of hygiene, safety, and sustainability. The domestic halal industry has grown rapidly, particularly in the sectors of food, halal cosmetics, modest fashion, and Muslim-friendly tourism, though it continues to face challenges such as low halal literacy, regulatory limitations, certification costs, and underdeveloped supply chain infrastructure. Government support through the National Committee for Islamic Economy and Finance (KNEKS), international branding strategies, digital marketing, and cross-sectoral collaboration are crucial in strengthening Indonesia’s halal industry competitiveness. In conclusion, the halal lifestyle has great potential to become a strategic instrument for national economic development while positioning Indonesia as an inclusive and sustainable global halal hub.